Incubation period of wild type of SARS-CoV-2 infections by age, gender, and epidemic periods - Achangwa, Chiara; Park, Huikyung; Ryu, Sukhyun (Frontiers in Public Health, 2022)
Background: The incubation period of the coronavirus disease 2019 (COVID-19) is estimated to vary by demographic factors and the COVID-19 epidemic period. Objective: This study examined the incubation period of the wild type of SARS-CoV-2 infections by the different age groups, gender, and epidemic periods in South Korea. Methods: We collected COVID-19 patient data from the Korean public health authorities and estimated the incubation period by fitting three different distributions, including log-normal, gamma, and Weibull distributions, after stratification by gender, and age. To identify any temporal impact on the incubation period, we divided the study period into two different epidemic periods (Period-1: 19 January–19 April 2020 and Period-2: 20 April–16 October 2020), and assessed for any differences. Results: We identified the log-normal as the best-fit model. The estimated median incubation period was 4.6 (95% CI: 3.9 – 4.9) days, and the 95th percentile was 11.7 (95% CI: 10.2 – 12.2) days. We found that the incubation period did not differ significantly between males and females (p = 0.42), age groups (p = 0.60), and the two different epidemic periods (p = 0.77). Conclusions: The incubation period of wild type of SARS-CoV-2 infection during COVID-19 pandemic 2020, in South Korea does not likely differ on different age groups, sex and epidemic periods